PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI GOOGLE CLASSROOM TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS X MIPA 2 SMA NEGERI 12 MAKASSAR - Suci Harianti; Sitti Rabiah; Ihramsari Akidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine whether there is an effect of using Google Classroom application learning media on the learning outcomes of students in class X SMA Negeri 12 Makassar. This type of research uses a quantitative approach, with a Pre-experimental design research method, a design that includes only one group or class that is given a pre and post test. The research design used in this study is Pre-Experimental one group pre-test post-test design, this is done on one class or one group without a control or comparison group. The research procedure includes the preparation stage, the implementation stage, grouping and analyzing data, concluding the research results. The Sig. value of 0.000 <0.05 was obtained, thus it can be decided that the average pretest and posttest are different. Because the value of Sig. <0.05, then H0 is rejected and H1 is accepted, which means that there is an effect of using learning media based on the google classroom application on aspects of the ability to write argumentation paragraphs and improve the learning outcomes of Indonesian language students in class X MIPA 2 SMA Negeri 12 Makassar.